PMP Penerapan Teknologi Tepat Guna Irigasi Sprinkler Berbasis IoT dalam Upaya Peningkatan Produksi di KWT Seruni Kelurahan Buntusu Kec. Tamalanrea Kota Makassar - Muhlis, Muhlis; Fatmawati, Fatmawati; Armus, Rakhmad; Zulfi, M.; Zhalianti, Desvira; Sappewali, Sappewali (COVIT (Community Service of Tambusai), 2023)
The Seruni Women's Farmers Group (KWT) whose address is at Bumi Tamalanrea Permai Housing Block G, Buntusu Village, Tamalanrea District, Makassar City was formed on March 12 2013, this KWT is chaired by Hj. Hartinawati, assisted by A. Emilda as Secretary and Hj. Zaenab as treasurer and 27 other members were formed from the Food Security program with the aim of realizing food self-sufficiency. This KWT utilizes empty land which is a public facility (Field) in the BTP Bloh H housing complex. Seruni KWT focuses on horticultural plants, especially vegetables, considering that the planting area is not very large, only using a green house. ccording to the results of an interview with the chairman of KWT Hj. Hartinawati said that Seruni KWT is urban farming in nature because it is located in the middle of an urban settlement and consists of housewives who have other routines so it has not been managed optimally. The main problem is related to production, namely the cultivation aspect in terms of maintenance, the lack of personnel in charge of carrying out maintenance, especially watering. The solution offered to overcome partner problems related to sustainable maintenance is the creation of IoT-based sprinkler irrigation for watering with the aim of making efficient use of water, time and labor. The approach method for solving the problem is the delivery of theoretical material regarding the use of IoT-based sprinkler irrigation, and marketing techniques. and continued with a demonstration and practice of designing an IoT-based sprinkler irrigation system carried out by KWT members. The expected target of this activity is: partners can increase their farming results and become a pilot project for urban fa rming activities. Keywords : Sprinkler, Farming, KWT, IoT